2020
DOI: 10.1080/09687637.2020.1832962
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption in aquatic settings: a mixed-method study exploring young adults’ attitudes and knowledge

Abstract: Attitudes 3 questions containing 19 statements 22 -24 Five-point Likert Scales  Can You Swim Survey (Moran et al., 2012; Petrass et al., 2012)  Alcohol and aquatic activity surveys and research findings (Hamilton & Schmidt, 2014; Sinkinson, 2014)  Survey on young adults' attitudes towards alcohol (Midford et al., 2000) and risky driving (Delcher et al., 2013; Ulleberg & Rundmo, 2003)  Psychometric scale of risk taking (Weber et al., 2002) Knowledge 10 Questions (13 including all UK and Australian versions)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In high-income countries, young adults (aged 15-24 years) are over-represented in drowning statistics, with alcohol consumption identified as a key risk factor for this age group. 5,14 However, very few studies have investigated the determinants of young adults' alcohol use in aquatic contexts (eg [15][16][17]. Coronial records of alcohol-related drownings in Australia demonstrated that purposefully jumping into the water was the most common activity of young adults (aged 18-24 years) prior to drowning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In high-income countries, young adults (aged 15-24 years) are over-represented in drowning statistics, with alcohol consumption identified as a key risk factor for this age group. 5,14 However, very few studies have investigated the determinants of young adults' alcohol use in aquatic contexts (eg [15][16][17]. Coronial records of alcohol-related drownings in Australia demonstrated that purposefully jumping into the water was the most common activity of young adults (aged 18-24 years) prior to drowning.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this evidence clarifying that young adults consume alcohol in aquatic contexts, previous studies have neglected to qualitatively explore young adults' behaviours, attitudes and knowledge associated with alcohol use in aquatic contexts. 17 More recent qualitative work has indicated that young Australians regularly mix alcohol and aquatic activity and cite this as a cultural norm, despite acknowledging and demonstrating awareness of the risks. 16 While this information is insightful in identifying a problem and contributes to the development of knowledge associated with understanding reasons for involvement, gaps remain regarding what young adults perceive as risky and what factors contribute to their involvement in alcohol-influenced aquatic activity (defined as activities in and on the water following/during the consumption of alcohol, and while alcohol effects could be influential on the individual).…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies described the self-reported prevalence of alcohol use around water in young people, with rates ranging from 25% to 61% [6,10,23,24,[30][31][32][33][34]. In general, the prevalence of self-reported alcohol use around water was greater in qualitative studies [10,30,33] than in those with a cross-sectional design [6,23,24,[32][33][34]. A further study by Peden and colleagues collected objective measurements of alcohol use around water by breathalysing river users [35].…”
Section: Prevalence Of Alcohol Use By Young People In Aquatic Environ...mentioning
confidence: 99%
“…The most frequently self-reported study limitations included a lack of generalisability due to the homogeneity and/or size of the sample [6, 10, 13, 23, 24, 30-33, 35, 36, 47], the possibility of social desirability bias [6,10,23,24,30,[32][33][34][35][36]47], and the self-report nature of data collection [6,24,25,32,35,36,38]. Other limitations relating to sampling included convenience sampling [31,34,47] and the possibility of participation bias, whereby only those who thought the study was relevant to them (e.g., those who drink alcohol) may have chosen to participate [35].…”
Section: Self-reported Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation